Exploring the Role of Education and Exports in Indonesia’s Economic Growth - Jumhur Jumhur (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
The assumption that education positively influences economic growth remains weakly supported. Therefore, this study aims to examine the extent to which education levels explain economic growth by incorporating foreign direct investment, credit, exports, and unemployment as mediating variables. The analysis uses time-series data for Indonesia from 1991 to 2018, obtained from the World Bank’s World Development Indicators. The results show that basic education has a negative but statistically insignificant effect on economic growth. In contrast, secondary and higher education have positive and significant effects, with higher education demonstrating the strongest influence. Furthermore, exports significantly mediate the effects of primary and higher education on economic growth, while no mediating variables significantly explain the impact of secondary education. These findings imply that greater investment in secondary and higher education is crucial for promoting sustainable long-term economic growth and strengthening export performance.